Modelos de inversión social para empresas mineras: experiencias y propuestas - Mogrovejo Álvarez, Mirella (2007)
Peru is experiencing a boom through growing mine operations and projects. This has created expectations among the benefi ts that activity may create for the mines’ neighboring communities. Although in most cases results have not been very encouraging, this paper seeks to demonstrate whatever progress has been made in the mining companies’ social management, and the scope of their proposals for improvement by presenting and comparing successful social investment models used in Peru in recent years. It also examines the issue of the mining industry’s voluntary contributions, social contributions and social trust funds, and explains how the money is allocated.